Handedness, footedness and ski-side dominance in elite corss-country skiers - Hébert-Losier, K.; Holmberg, H. C.; Stöggl, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Laterality in sports is researched in motor learning, injury prevention, and biomechanics. Handedness and footedness in sports is commonly addressed in isolation, and investigates tasks that are predominantly upper (baseball) or lower (soccer) body dependent. In contrast, cross-country skiing (XCS) is a whole-body exercise that relies on arms and legs. Although asymmetric techniques are used in XCS, and side preferences are observed; little research has explored lateralization in skiers. Thus, the aim was to investigate if handedness and footedness correlated with ski-side preference. Methods: Eleven male elite XC skiers (28±5 yrs) completed a standard handedness (n=12 items), footedness (n=10 items), and ski-side dominance (n=11 items) questionnaire. Each item could be answered right, left, or either based on the side that was habitually used to perform a given task (i.e. write, kick a ball, preferred ski-curve). Each response was entered into a contingency table and measures of associations were expressed using correlation coefficients. Significance level was P<.05. Results: Six of the 11 items on ski-side dominance were correlated to handedness or footedness items (all P<.05), but no ski-side item correlated with hand/foot items simultaneously. The dominant side in steep uphill skating (V1) was associated with 3 handedness items (r=.63). Using V1 at 15k race velocity, the dominant side was correlated to 9 of the 12 handedness items (r =.65). At peak velocity, the dominant V1 side correlated with the leg used to balance on one foot (r =.82). The leg used to accept weight when standing, stand on one foot, and step onto a chair or push a shovel into the group correlated with the dominant kick leg in kick double poling, preferred curve direction at a high velocity, and leg pushed forward at the end of a sprint race (r =.69 to .91), respectively. Discussion: XCS is biomechanically complex, and relies on upper and lower body. Certain ski techniques favor one side of the body, and some were correlated with the sides used in daily tasks. Certain associations between ski-side and hand/foot dominance were more intuitive than others. For instance, several hand items were correlated with the dominant side in V1. Foot items were correlated with the preferred kick leg in kick double poling, which presumably reflects the need for the skis to grip to the snow. Correlations changed with skiing velocities, suggesting that velocity is an important factor in lateralization. This was a first attempt to address laterality in skiers using validated handedness and footedness questions, in addition to a ski-specific questionnaire. Standard, valid, and reliable ski-side questions should be used in future research to increase the understanding of lateralization in humans.